Blasphemy and Censorship. The Historical Importance of Passive and Active Models - David Nash (Revue LISA)
This article revisits some of the author’s established theorising around the issue of the crime of blasphemy and how it has been interpreted in the west since the medieval period. In particular Nash’s theory of “passive” and “active” blasphemy is examined to see how far this analysis might be extended to embrace and potentially explain the wider phenomenon of censorship. Through examining the history of blasphemy and its formulation by individuals and institutions in authority it potentially becomes possible to explain and contextualise the motivation of those who censor. The issue of power and intention loom large and are investigated through dialogues with the ideas of Foucault and Norbert Elias. The article ends by speculating how the idea of the “passive”, in which individuals simply expect protection from harm without playing a part in assessing or gauging its level of real threat, has returned to the perception of blasphemy in the 21st century. Likewise speculation about whether this is a potential issue in the wider history and contemporary study of wider censorship is invited.